1982
DOI: 10.1016/0021-9797(82)90308-3
|View full text |Cite
|
Sign up to set email alerts
|

Micellization and intermicellar interactions in aqueous sodium dodecyl benzene sulfonate solutions

Abstract: Quasielastic light scattering was used to investigate the size and shape of sodium dodecyl benzene sulfonate (SDBS) micelles in aqueous solutions. Measurements were made as a function of temperature and NaC1 and SDBS concentrations. Light scattering data indicate that the micelles are spherocylinders with a semiminor axis of 22 A. The length of the micelles increases strongly with salt concentration and decreases with temperature. The minimum micelle has an aggregation number of n o = 28 and a hydrodynamic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 17 publications
6
30
1
Order By: Relevance
“…Other studies with an AOS containing almost equal amounts of C 14 , C 16 , and C 18 revealed a CMC of 4.2 mM (19). The composition of the AOS used by the different research groups appears to be the cause of the differences in the results.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Other studies with an AOS containing almost equal amounts of C 14 , C 16 , and C 18 revealed a CMC of 4.2 mM (19). The composition of the AOS used by the different research groups appears to be the cause of the differences in the results.…”
Section: Introductionmentioning
confidence: 67%
“…Surface tension experiments yielded a value for the CMC of about 1.6 mM for an AOS with mostly fractions of C 16 and C 18 (29). Other studies with an AOS containing almost equal amounts of C 14 , C 16 , and C 18 revealed a CMC of 4.2 mM (19).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, intermicellar interaction of surfactants in aqueous solutions has been investigated by many workers [29][30][31][32][33][34][35][36]. Dynamic light scattering of ionic micdles in aqueous solutions was measured and the results were analyzed on the basis of the DLVO theory [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The most signifi cant aspect is the outstanding exfoliation capability of the bolaamphiphilic perylene derivative 1 and the amphiphilic perylene derivative 3 approaching 76% (at pH = 10). Please note that this is by a factor of fi ve higher than the commonly used detergent SDBS which forms micelles with a radius of 3 nm [ 101 ] that allows inclusion of small nanotube bundles. [ 102 ] Since nanotube individualization is the key factor for any separation scenario, improving the exfoliation will also ultimately have the potential to enhance sorting yields.…”
Section: Progress Reportmentioning
confidence: 98%